Regional development of rural tourism: The case of the Gorska Hrvatska Region - Nina Baković (Naše gospodarstvo / Our Economy, 2020)
An approach to sustainable tourism through clusters is considered an appropriate strategy in less-developed rural areas of tourist-oriented countries, such as Croatia. This paper clarifies the key challenges of the development of tourism clusters in the region of Gorska Hrvatska and provides new data for an approach to sustainable rural tourism development. Using available secondary data from governmental bodies, non-governmental organizations, protected areas of Gorska Hrvatska, and primary data of the Lika Destination Cluster, the paper explores the key challenges of developing a cluster of tourism and selective forms of tourism. Most tourism clusters in Croatia have remained in the first phase of development for years, even though this approach has failed to to achieve significant results. The key benefits of networking and branding in rural areas are identified and defined, but these potentials are still largely underutilized. The objective of this study is to provide practical recommendations to the Croatian tourism industry on how to learn from the suggested best practices and how to implement them effectively. For that purpose, the case of sustainable tourism located in the Gorska Hrvatska region, called the Lika Destination Cluster is analyzed.
Keywords: M20; M21; Q56; 330; rural tourism; Gorska Hrvatska; clusters; protected areas; competitiveness; Lika Destination Cluster